Technology as enabler of the automation of work? Current societal challenges for a future perspective of work; A tecnologia como facilitadora da automaç\~ao do trabalho? Desafios sociais atuais para uma vis\~ao do futuro do trabalho - Bettina-Johanna Krings; António Moniz; Philipp Frey (Revista Brasileira de Sociologia, 2021)
Due to the innovative possibilities of digital technologies, the issue of increasing automation is once again on the agenda – and not only in the industry, but also in other branches and sectors of contemporary societies. Although public and scientific discussions about automation seem to raise relevant questions of the “old” debate, such as the replacement of human labor by introducing new technologies, the authors focus here on the new contextual quality of these questions. The debate should rethink the relationship between technology and work with regard to quantitative and qualitative changes in work. In this article, our example will be the introduction of automation in industry, which has been reflected in the widely recognized study by Frey and Osborne in 2013. They estimated the expected impacts of future computerization on US labor market outcomes as very high, specifically regarding the number of jobs at risk. Surprisingly, this study was the starting point of an intensive international debate on the impact of technologies on the future of work and the role of technological change in working environments. Thus, according to the authors, “old” questions remain important, but they should be reinterpreted for “new” societal demands and expectations of future models of work. – – Em virtude das possibilidades de inovaç\~ao colocadas pelas tecnologias digitais, vem crescendo o debate sobre o aumento da automaç\~ao – n\~ao apenas na indústria, mas também em outros ramos e setores das sociedades contemporâneas. Embora os debates público e científico sobre automaç\~ao pareçam focar quest\~oes relevantes do “antigo” debate, como a substituiç\~ao do trabalho humano pela introduç\~ao de novas tecnologias, os autores concentram-se, aqui, no novo aspecto contextual dessas quest\~oes. O debate precisa repensar a relaç\~ao entre tecnologia e trabalho no que concerne às mudanças quantitativas e qualitativas no trabalho. Neste artigo, nosso exemplo será a introduç\~ao da automaç\~ao na indústria, que se refletiu no estudo amplamente reconhecido de Frey e Osborne, de 2013. Eles estimaram impactos profundos da futura informatizaç\~ao sobre os desfechos do mercado de trabalho dos EUA, particularmente em relaç\~ao ao número de empregos em risco. Surpreendentemente, este estudo foi o ponto de partida para um intenso debate internacional sobre o impacto das tecnologias no futuro do trabalho e o papel da mudança tecnológica nos ambientes de trabalho. Assim, de acordo com os autores, embora as “velhas” quest\~oes permaneçam importantes, elas devem ser reinterpretadas considerando as “novas” demandas sociais e expectativas de modelos futuros de trabalho.
Keywords: O33; O35; M11; L60; 300; new models of work; transformation of work; technical unemployment; automation